Transformasi Digital dalam Layanan BK: Studi Audit Digital Counseling Reality di SMA - Epenta Sitepu; Evan Raja Natanael Siregar; Lovian Malona Br. Manullang; Kristian Nehemia Sianipar (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
The rapid growth of digital technology has encouraged school counseling services to adapt to the needs of students who are highly connected to digital media. This study aimed to audit the implementation of Digital Counseling Reality in counseling services at SMA Negeri 15 Medan to examine the level of technology integration within counseling practices. Data were collected through interviews, observations, document reviews, and digital audit instruments involving the counseling coordinator, school counselors, and students. The findings revealed that the school has utilized social media, consultation platforms, digital assessments, online counseling, and data-based evaluations in delivering counseling services. School counselors demonstrated positive attitudes toward e-counseling and showed adequate technological competence, while students expressed positive perceptions regarding comfort, accessibility, and the necessity of digital counseling services. The audit result reached a score of 23, placing the school in the digital-integrated category. These findings indicate that technology has become an essential component of counseling services and contributes to improving service quality, accessibility, and effectiveness for students.